CD8(+) T Cell Immune Response in Immunocompetent Mice during Zika Virus Infection - Huang, Huarong (J Virol, 2017)
Zika virus (ZIKV) infection causees neurologic complications, including Guillain-Barré syndrome in adults and central nervous system (CNS) abnormalities in fetuses. We investigated the immune response, especially the CD8(+) T cell response in C57BL/6 (B6) wild-type (WT) mice, during ZIKV infection. We found that a robust CD8(+) T cell response was elicited, major histocompatibility complex class I-restricted CD8(+) T cell epitopes were identified, a tetramer that recognizes ZIKV-specific CD8(+) T cells was developed, and virus-specific memory CD8(+) T cells were generated in these mice. The CD8(+) T cells from these infected mice were functional, as evidenced by the fact that the adoptive transfer of ZIKV-specific CD8(+) T cells could prevent ZIKV infection in the CNS and was cross protective against dengue virus infection. Our findings provide comprehensive insight into immune responses against ZIKV and further demonstrate that WT mice could be a natural and easy-access model for evaluating immune responses to ZIKV infection. IMPORTANCE ZIKV infection has severe clinical consequences, including Guillain-Barré syndrome in adults, microcephaly, and congenital malformations in fetuses and newborn infants. Therefore, study of the immune response, especially the adaptive immune response to ZIKV infection, is important for understanding diseases caused by ZIKV infection. Here, we characterized the CD8(+) T cell immune response to ZIKV in a comprehensive manner and identified ZIKV epitopes. Using the identified immunodominant epitopes, we developed a tetramer that recognizes ZIKV-specific CD8(+) T cells in vivo, which simplified the detection and evaluation of ZIKV-specific immune responses. In addition, the finding that tetramer-positive memory CD8(+) T cell responses were generated and that CD8(+) T cells can traffic to a ZIKV-infected brain greatly enhances our understanding of ZIKV infection and provides important insights for ZIKV vaccine design.